Biostimulators: A New Trend towards Solving an Old Problem - Posmyk, Małgorzata M.; Szafrańska, Katarzyna (Frontiers in Plant Science, 2016)
Stresses provoked by adverse living conditions are inherent to a changing environment (climate change, anthropogenic influence) and they are basic factors that limit plant development and yields. Agriculture always struggled with this problem. The survey of nontoxic, natural, active substances useful in protection and stimulation of plants growing under suboptimal and even harmful conditions, as well as searching for the most effective methods for their application, will direct our activities towards sustainable development and harmony with nature. It seems highly probable that boosting natural plant defence strategies by applying biostimulators will help to solve an old problem of poor yield in plant cultivation, by provoking their better growth and development even under suboptimal environmental conditions. This work is a concise review of such substances and methods of their application to plants.